Role of Neural Cell Adhesion Molecule and Polysialic Acid in Mouse Circadian Clock Function - Shen, Huaming (J Neurosci, 1997)
The suprachiasmatic nuclei (SCN) express the highly polysialylated form of the neural cell adhesion molecule (NCAM) that has been proposed to promote plasticity in the adult brain. To investigate a role for NCAM in SCN circadian clock function, we examined the daily locomotor rhythm of mice homozygous for a mutation,Ncam(tm1Cwr), which results in deletion of the NCAM-180 isoform that in brain carries polysialic acid (PSA). Mutant mice entrained well to a 12 hr light/dark cycle but exhibited a significantly shortened free-running period and longer activity duration under constant darkness (DD) than did wild-type mice. By the third week of DD treatment, circadian rhythmicity in the mutant was abolished. Immunocytochemical analyses of the mutant SCN revealed an abnormal number and distribution of vasoactive intestinal polypeptide-producing neurons, suggesting a developmental effect of the mutant phenotype; however, a direct physiological effect of the mutation on clock function was indicated by the fact that removal of PSA from adult wild-type SCN by microinjection of endoneuraminidase shortened the free-running period to a similar extent as in the mutant. Together, these data indicate critical roles for NCAM and PSA in the development and physiology of the mammalian SCN circadian clock.